Adolescent Binge-Type Ethanol Exposure in Rats Mirrors Age-Related Cognitive Decline by Suppressing Cholinergic Tone and Hippocampal Neurogenesis - Reitz, Nicole L.; Nunes, Polliana T.; Savage, Lisa M. (Frontiers in Behavioral Neuroscience, 2021)
Heavy alcohol consumption followed by periods of abstinence (i.e., binge drinking) during adolescence is a concern for both acute and chronic health issues. Persistent brain damage after adolescent intermittent ethanol exposure in rodents, a model of binge drinking, includes reduced hippocampal neurogenesis and a loss of neurons in the basal forebrain that express the cholinergic phenotype. The circuit formed between those regions, the septohippocampal pathway, is critical for learning and memory. Furthermore, this circuit is also altered during the aging process. Thus, we examined whether pathology in septohippocampal circuit and impairments in spatial behaviors are amplified during aging following adolescent intermittent ethanol exposure. Female and male rats were exposed to intermittent intragastric gavage of water (control) or 20% ethanol (dose of 5 g/kg) for a 2 day on/off cycle from postnatal days 25 to 55. Either 2 (young adult) or 12-14 (middle-age) months post exposure, rats were tested on two spatial tasks: spontaneous alternation and novel object in place. Acetylcholine efflux was assessed in the hippocampus during both tasks. There was no adolescent ethanol-induced deficit on spontaneous alternation, but middle-aged male rats displayed lower alternation rates. Furthermore, male rats exposed to ethanol during adolescence had blunted behavioral evoked acetylcholine during spontaneous alternation testing. All ethanol-exposed rats displayed suppression of the cholinergic neuronal phenotype. On the novel object in place task, regardless of sex, ethanol-exposed rats performed significantly worse than control-treated rats, and middle aged-rats, regardless of sex or ethanol exposure, were significantly impaired relative to young adult rats. These results indicate that male rats display earlier age-related cognitive impairment on a working memory task. Furthermore, male rats exposed to ethanol during adolescence have blunted behavior-evoked hippocampal acetylcholine efflux. In addition, middle-aged and ethanol-exposed to rats, regardless of sex, are impaired at determining discrete spatial relationship between objects. This type of pattern separation impairment was associated with a loss of neurogenesis. Thus, binge-type adolescent ethanol exposure does affect the septohippocampal circuit, and can accelerate age-related cognitive impairment on select spatial tasks.